(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines the territorial varieties of English pronunciation across different geographical regions where English serves as a primary or official language. The research explores phonetic and phonological variations that characterize major English dialects, analyzing systematic differences in vowel systems, consonant realizations, prosodic patterns, and accent features. Through comprehensive examination of British, American, Australian, Canadian, and other regional varieties, this paper investigates the historical, social, and linguistic factors that have shaped distinct pronunciational patterns. The study contributes to understanding dialectal diversity within English and its implications for language teaching, communication, and linguistic identity.